Monitoramento das cargas de treinamento no tenis de elite - Coutts, A. J.; Vitasovic Gomes, R.; Viveiros, L.; Saldanha Aoki, M. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2010)
Training load (TL) is influenced by both training volume and training intensity. A precise understanding of the TLs completed during training is crucial to achieve desirable training outcomes and to avoid overtraining. TL can be monitored in many different ways; however, we recommend the session-rate of perceived exertion (session-RPE) method for quantifying TL because of its low cost and because it is easy to understand and relatively simple to implement. In this report, we provide data regarding TLs collected during the 2008 Roland Garros Tournament. Our experience in tennis suggests the session-RPE method to be a valuable tool that can be used to control training and to avoid excessive TLs. We also believe that accurate monitoring of TL will enable the coach to better understand of the sports training process, ultimately leading to the improvement of performance.